2012
DOI: 10.5152/akd.2012.159
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnesium and vitamin E pre-treatments on irradiation-induced oxidative injury of cardiac and pulmonary tissues in rats: a randomized experimental study

Abstract: The effect of magnesium and vitamin E pre-treatments on irradiationinduced oxidative injury of cardiac and pulmonary tissues in rats: a randomized experimental studyProfilaktik magnezyum ve E vitamini uygulamasının sıçanlarda ışınlamaya bağlı kalp ve akciğer dokusunda gelişen oksidan hasara etkileri: Randomize deneysel bir çalışma ABSTRACTObjective: The aim of this study was to investigate the effect of pre-treatment with the free radical scavenging molecules, magnesium and vitamin E, on lipid peroxidation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Therefore, Vit E can reduce the risk of coronary heart disease [14]. Many studies have identified the antioxidant and antiatherosclerotic properties of vitamin E in animals [71][72][73][74]. In 2001, Ferre et al found that a diet containing vitamin E, palm oil, or sunflower oil would reduce the range of pathological changes in the aorta [71].…”
Section: Antioxidant Source Mechanism Effectmentioning
confidence: 99%
“…Therefore, Vit E can reduce the risk of coronary heart disease [14]. Many studies have identified the antioxidant and antiatherosclerotic properties of vitamin E in animals [71][72][73][74]. In 2001, Ferre et al found that a diet containing vitamin E, palm oil, or sunflower oil would reduce the range of pathological changes in the aorta [71].…”
Section: Antioxidant Source Mechanism Effectmentioning
confidence: 99%
“…Hydroxyproline is an important component of collagen which correlates to the severity of the lung fibrosis (17), and MDA is an important lipid peroxide that reflects the damage caused by oxygen free radical (18). Our results showed that the content of hydroxyproline and MDA in lung tissue in the radiation group was significantly higher than that in the control group.…”
Section: Rübe Et Al Have Shown That Bronchial Epithelial Cells Couldmentioning
confidence: 64%